Integral Inequalities Involving Strongly Convex Functions. (11th June 2018) - Song, Ying-Qing; Adil Khan, Muhammad; Zaheer Ullah, Syed; Chu, Yu-Ming
Abstract : We study the notions of strongly convex function as well asF -strongly convex function. We present here some new integral inequalities of Jensen's type for these classes of functions. A refinement of companion inequality to Jensen's inequality established by Matić and Pečarić is shown to be recaptured as a particular instance. Counterpart of the integral Jensen inequality for strongly convex functions is also presented. Furthermore, we present integral Jensen-Steffensen and Slater's inequality for strongly convex functions.